Ontology-Learning-Based Focused Crawling for Online Service Advertising Information Discovery and Classification - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Springer - Verlag, 2012)
Online advertising has become increasingly popular among SMEs in service industries, and thousands of service advertisements are published on the Internet every day. However, there is a huge barrier between service-provider-oriented service information publishing and service-customer-oriented service information discovery, which causes that service consumers hardly retrieve the published service advertising information from the Internet. This issue is partly resulted from the ubiquitous, heterogeneous, and ambiguous service advertising information and the open and shoreless Web environment. The existing research, nevertheless, rarely focuses on this research problem. In this paper, we propose an ontology-learning-based focused crawling approach, enabling Web-crawler-based online service advertising information discovery and classification in the Web environment, by taking into account the characteristics of service advertising information. This approach integratesan ontology-based focused crawling framework, a vocabulary-based ontology learning framework, and a hybrid mathematical model for service advertising information similarity computation.